2004
DOI: 10.1002/mabi.200400093
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Endosomolytic Properties of Poly(amidoamine) Block Copolymers

Abstract: Summary: The poly(amidoamine)s (PAAs) ISA 1 and ISA 23 display pH‐dependent conformational change and pH‐dependent membrane perturbation. These properties confer potential for use as endosomolytic polymers for intracytoplasmic delivery of toxins and genes. Both polymers are relatively non‐toxic, and moreover ISA 23 has the beneficial property in vivo, of being non hepatotropic when administered intravenously. Although ISA 23 and ISA 1 demonstrate ability to transfect cells, ISA 1 is also able to promote intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 37 publications
(53 reference statements)
1
33
0
Order By: Relevance
“…Thus, this thermo-responsive property has been utilized as an ''on-off" switch for drug release, attachment/detachment of cells, and so on [16][17][18][19]. Besides, pH is another important stimulus, which has been used to develop pH-responsive materials [4,20,21]. Weakly acidic or alkalescent polymers containing carboxylic acid or amine are the pH-responsive candidates that undergo a change in the ionization state on the variation of pH values, resulting in a reversible change between hydrophilicity and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, this thermo-responsive property has been utilized as an ''on-off" switch for drug release, attachment/detachment of cells, and so on [16][17][18][19]. Besides, pH is another important stimulus, which has been used to develop pH-responsive materials [4,20,21]. Weakly acidic or alkalescent polymers containing carboxylic acid or amine are the pH-responsive candidates that undergo a change in the ionization state on the variation of pH values, resulting in a reversible change between hydrophilicity and hydrophobicity.…”
Section: Introductionmentioning
confidence: 99%
“…ISA23 in particular has been proven to be endowed with stealth-like properties without selectively concentrating in the liver [44], while a significant portion of AGMA1 did show hepatic localization after intravenous injection in mice [42]. In intracellular compartments where the pH decreases to 6.5 (endosomes) and then to 5.0 (lysosomes), PAAs become prevailingly cationic and display endosomolytic properties [72]. Fluorescence microscopy revealed colocalization of ISA1 and ISA23 with Lysotracker, a marker for lysosome and late endocytic structures, and ISA1 also colocalized with the Early Endosomal Antigen 1 that accumulates in early endocytic structures [45].…”
Section: Paas For the Targeted Delivery Of Antimalarial Drugsmentioning
confidence: 99%
“…10,11 Recent studies have demonstrated that modulation of the PAAs hydrophobicity inuenced binding of the polymer to DNA. 12,13 Although several studies have reported intracellular delivery of proteins with PAAs, [14][15][16] there is no report investigating the interaction of the poly(amidoamine)s with proteins. Polyelectrolyte-protein complexation has been studied in the context of protein purication, enzyme immobilisation, sensor development or stimuli responsive systems.…”
Section: 3mentioning
confidence: 99%
“…Although poly(amidoamine)s have been used to promote intracellular delivery, 5,11,14,15 the interactions between the polymers and the protein and their effect on the protein stability are poorly understood. Protein-polyelectrolyte complexation may results from different types of interactions, including ionic and hydrophobic interactions, hydrogen bonding or coulombic forces.…”
Section: Interaction With Bsamentioning
confidence: 99%